PERTANGGUNGJAWABAN HUKUM TERHADAP PELAKU PENIPUAN ONLINE MELALUI PLATFORM FACEBOOK - Wening Ayu Pratiwi; Achmad Edi Subiyanto (Fakultas Hukum Universitas Kristen Indonesia, 2026)
The advancement of information technology has significantly increased online buying and selling activities through various digital platforms, including social media such as Facebook. Along with this convenience, cases of online fraud have also risen and caused losses to consumers. This study aims to examine the forms of legal liability of online fraud perpetrators on the Facebook platform and to analyze the extent to which the implementation of the Law on Information and Electronic Transactions (ITE Law) provides legal protection for victims. The research method used is normative legal research with a statutory approach and a case approach, particularly Decision Number 167/Pid.Sus/2024/PN Bjm. The results show that online fraud perpetrators can, in principle, be held legally accountable under Article 28 paragraph (1) in conjunction with Article 45A paragraph (1) of the ITE Law as a special legal provision. The application of the ITE Law has provided legal protection for victims, especially through the recognition of electronic evidence and the imposition of criminal sanctions. However, such protection has not yet been fully optimal because it still focuses primarily on punishing offenders and has not comprehensively regulated mechanisms for the recovery of victims’ losses. Therefore, synergy between the ITE Law and the Consumer Protection Law is necessary to achieve more effective and equitable legal protection.Online Fraud